A COVID-19 Public Health Silver Lining? Reductions in Driving under the Influence Arrests and Crashes in Miami-Dade County. Issue 10 (3rd October 2022) - Piquero, Alex R.; Kurland, Justin; Piquero, Nicole Leeper; Talpins, Stephen K.
ABSTRACT: The health crisis that began in early 2020 has generated a large amount of interest in the effect of COVID-19 on public health. The majority of this work has centered around trying to better understand how the virus spreads, where it spreads, who is at risk and when, in order to provide evidence-based guidance to the public, and stop the pandemic. The Centers for Disease Control has continued to report the largely somber findings; however, there are silver linings. The temporary reduction in daily global CO2 emissions was one of these, but there are others. In this case study on Miami-Dade County, Fl, a regression discontinuity model is used to highlight reductions in both drunk driving crashes and driving under the influence arrests. While we observed immediate reductions in both crashes and arrests as a result of the March 2020 lockdown, more importantly over the duration of the year since the lockdown we observed a staggering reduction of over 800 fewer driving under the influence arrests and almost 150 alcohol-related motor-vehicle crashes.